Turquoise hydrogen generation through catalytic decomposition of methane by modeling approach - Tong, Sirui (Nanyang Technological University, 2024)
Hydrogen stands as a pivotal clean energy vector, offering a versatile and environmentally sustainable alternative to conventional fossil fuels. Its potential to enable deep decarbonization across diverse sectors like transportation, industry, and power generation is increasingly recognized. Traditional methods of hydrogen production, however, pose inherent challenges, chiefly the unavoidable emissions of CO2. Enterprising solutions, particularly within the realm of "turquoise hydrogen," spotlight the catalytic decomposition of methane (CDM) as a transformative technology. This process directly converts methane into hydrogen and solid carbon (CH4 → C + 2H2), distinctly curbing emissions and positioning CDM as a critical conduit toward the zero-emission "green hydrogen" phase. While extant experimental studies have offered insights into catalyst development, reaction kinetics, and mechanisms, a comprehensive exploration of varied reaction conditions' impact on performance remains uncharted territory. To bridge this gap, numerical simulations emerge as a potent tool capable of amassing intricate reaction-related data, proposing optimization strategies, and, in turn, guiding subsequent experimental endeavors.